The use of www.123listening.com to teach listening skill for the fourth-grade students - Istiqomah, Istiqomah; Affini, Laily Nur; Wahyuni, Sri (Indonesian Journal of Education and Pedagogy, 2024)
Building strong listening skills is crucial for academic and social success, but many teachers struggle with teaching this skill. To address this, websites like www.123listening.com provide resources and activities to improve listening skills. This study is aimed to find out the impact of listening material from www.123listening.com in teaching listening. The participants of this study were fourth grade students of SDN 1 Botomulyo which consisted of 28 students. Quantitative research designs were applied with test and questionnaire as the instruments to obtaining the data. Pre-test and post-test data were analysed statistically using SPSS while the questionnaire results were analysed descriptively. The result of the post-test showed that students’ scores were getting higher after learning about listening skill using material from www.123listening.com. It means that the use of material from www.123listening.com is effective in teaching listening. Whereas based on the questionnaire, most students felt very enjoyable on the learning. It implies that technology platforms can be alternative learning strategy for teachers to enhance students’ language skills and enthusiasm in learning.